2012
DOI: 10.1007/s00394-012-0430-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D metabolism, functions and needs: from science to health claims

Abstract: Vitamin D, through food fortification and supplementation, is a promising new health strategy and thus provides opportunities for food industry and nutrition researchers to work together towards determining how to achieve this potential health benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 78 publications
0
115
0
12
Order By: Relevance
“…Esta ação antiproliferativa da 1,25(OH)2D tem sido explorada como estratégia terapêutica para vários tipos de câncer 22,26 .…”
Section: Vitamina D E Câncerunclassified
See 2 more Smart Citations
“…Esta ação antiproliferativa da 1,25(OH)2D tem sido explorada como estratégia terapêutica para vários tipos de câncer 22,26 .…”
Section: Vitamina D E Câncerunclassified
“…É sabido que a 1,25(OH)D aumenta as propriedades antimicrobianas de monócitos e a capacidade fagocitária dos macrófagos 26 .…”
Section: Vitamina D E Doenças Autoimunesunclassified
See 1 more Smart Citation
“…Immune cells carry VDR and 1α-hydroxylase, which produces the active metabolite 1.25(OH)2D through local synthesis and heightens immunomodulatory properties [8]. Increasing evidence indicates that vitamin D deficiency may cause dysregulation of the innate and adaptive immune systems and promote microinflammation [22].…”
Section: Vitamin D and Immune Regulationmentioning
confidence: 99%
“…[2] The serum vitamin D level is determined by skin synthesis through sun exposure and/or dietary intake. [3] Access this article online The sources of vitamin D are cutaneous production and diet, only some foods naturally contain it, and few are rich in vitamin D. [4] Lifestyle and physical health factors associated with low vitamin D, such as smoking, increased body mass index, inactivity, and social withdrawal (likely resulting in decreased sunlight exposure), are all more frequent in people with psychosis. [5] There are several studies that have shown a correlation between psychosis and ethnicity, especially when dark skinned people immigrate to countries of higher latitude.…”
Section: Introductionmentioning
confidence: 99%